Um rastro de memória: terra, parentesco e ofícios na família Belém em Acari/RN (Séc. XVIII-XXI) - Santos, Jardelly Lhuana da Costa (2017)
This project has the objective to understand the process the delate of the presence of black people in Seridó, starting from comparative analysis of historical documents and the memories from Belém‟s family which is formed by domestics groups that came from a farm that has the biggest amount of slaves in XVIII century. Since of the beginning of the colonization african people are in Seridó, but their descendants have suffered a process of invisibilty, stigmatisation and the theft of their lands, that was taken by the big farmers. The genealogical trajetory of Belém‟s family, the memories from Mouras‟,Guiné and Belém were compared with historical documents. I going to describe how the “Belém‟s family” was build in a scar of slavery times. So, I will question this ethnographic datas and from that I will complete the empty spaces which exists in the documents(Wachtel, 1990). This search show a big diversity of statutes between african people in historical process, the existence of habits and jobs that bring to the past, despite the few registers of memory. The “vaqueiros”, “tropeiros”, women cooks and the others characters which had specialized functions participate, by the their knowledge and habits, the historical continuity of the presence of african population that was slavered in Seridó.